Socio-Economic System Evaluation of Ukrainian Black Sea: Array - Glubochenko, Kateryna; Nazarova, Liudmyla; Porudeyeva, Tatiana (Journal of Danubian Studies and Research, 2020)
The main idea of the paper is to offer a method of effectiveness analysis of regional socioeconomic system management in Ukraine. This study develops evaluation criteria for the assessment of intraregional differentiation of Ukrainian Black Sea regions. The goal of the research is to reveal the algorithm of the regional socio-economic system evaluation in order to find out the direction of necessary managerial strategy for a region. This was implemented via such methods as comparative analysis, interpretation of statistical indices of regional effectiveness, and structural analysis. The research results reveal that a chosen system of indicators forms a method to evaluate six levels (four zones) of effectiveness of regional socio-economic system management in Ukraine. Considering agriculture, food industry, pharmaceuticals, light industry, and tourism as the basic industries of the regions, the industrial structure of the regional socio-economic system of Ukrainian Black Sea regions in the context of its modernization according to the offered method was developed.